Muatan Berpikir Kritis Meta-Theoretical Aristoteles dalam Pembelajaran Asam-Basa di Lembaga Pendidikan Islam - Agung Nugraha; Irawan; Aan Hasanah (Universitas Insan Budi Utomo, 2023)
The content of critical thinking should be possessed by teachers because it benefits not only students but also the teachers themselves. Teachers play a crucial role in achieving the educational goals in developing students' critical thinking abilities. Many teachers fail to formulate the construct of critical thinking, assuming that understanding the development of critical thinking assessment is challenging, such as what will be measured. The purpose of this research is to measure the content of critical thinking in the Meta-Theoretical Aristoteles approach in Acid-Base Learning in Islamic Educational Institutions. The method used to compose this article is literature review (library research). Aristoteles values the importance of observation and experience in learning. In the context of learning, critical thinking should be based on careful observation and meticulous analysis of real experiences. By using critical thinking principles inspired by Aristoteles, educators can help students develop strong critical thinking skills, understand how to make strong arguments, and deepen their understanding of various subjects in the Acid-Base concept in Islamic educational institutions